Preservation assessment surveys: an interdisciplinary approach - Walker, Alison (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
In this paper I will discus a standard method of surveying collections to assess preservation need, how it has developed from a library model, to incorporate provision for archive collections, and how we are moving to apply the same methodology to museum collections. I will emphasise how the basic structure has been adapted to accommodate the requirements of the three domains.